Detection of sharks with the Gemini imaging sonar - Parsons, Miles; Parnum, Iain; Allen, K.; McCauley, Robert; Erbe, Christine (Australian Acoustical Society, 2014)
Limiting environmental impacts of marine industrial operations and mitigating hazardous encounters between humans and marine fauna have become increasingly important as anthropogenic activity expands. To this end, significant effort has been made to develop sonar imaging of fauna and to increase detection and identification ranges. A Tritech Gemini imaging sonar was used to observe sharks of 1.4 to 2.7 m length, at ranges from 1 to 50 m, in various water depths ≤15 m. Within 5 m, shark shape, length and swimming action were readily discernible. However, as range increased, knowledge of movement patterns was required to discriminate a 'shark-like' object, before the shark became purely an acoustic target at greater ranges, where visual confirmation of the target was necessary for identification. Once the seafloor is ensonified by the acoustic beam, seafloor backscatter can dominate the image and mask shark detection. The results presented concur with other active acoustic detection studies that, for a given frequency and noise level, maximum detection and identification ranges are reliant on system source level, beam pattern, bathymetry, and target size and acoustic reflectivity.